UNCOVERING THE DETERMINANTS OF CUSTOMERS' DECISION TO CHOOSE KURNIA LOANS OF KEDIRI CITY GOVERNMENT - Wicaksono, Adi; Anggraini, Reni (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 10 No 1 (2024): The 10th International Conference of Islamic Economics and Business (ICONIES 2024), 2024)
The financial inclusion index in Indonesia in 2020 was 81.4%. To increase this, the Kediri City Government launched the Kredit Usaha Melayani Warga (Kurnia) program on April 1, 2021. The interest rate is 2% per year, much lower than other loans such as the People's Business Credit (KUR) at 6%. According to the SOP, the Kurnia disbursement process takes 5 working days, longer than the average of other banks which is 1 working day. Since its implementation until December 31, 2023, the number of program participants is 659 customers. With a total disbursement of 10,533 billion Rupiah. This research aims to investigate the reasons why customers choose Kurnia. The findings are expected to contribute to the marketing management literature in financial institutions as well as policy inputs for management. An online questionnaire was used to collect feedback from a sample of 70 customers. Multiple regression was used to analyze the relationship between customer trust, service quality, interest rate and customer decision to choose credit. Findings of this study are that interest rates have a significant effect on loan decisions, while customer trust and service quality have the opposite effect. This proves that interest rates are still a reason for determining loan decisions, even though the process is longer